GEOGRAPHIC TONGUE: PATTERN OF PRESENTATION IN A SOUTH WESTERN NIGERIAN TEACHING HOSPITAL - Oyetola, E.O. (Ann Ib Postgrad Med, 2018)
BACKGROUND: Geographic tongue (GT) is one of the commonly seen lesions in Oral Medicine Clinic. It tends to show varying pattern of presentation. Excessive immune response and immune modulation has been implicated in the pathogenesis and this justified the use of steroid in the management. OBJECTIVE: This study describes the epidemiology, clinical presentations and treatment outcomes of the 21 cases of GT seen at the Oral Medicine Clinic of Obafemi Awolowo University Teaching Hospitals' Complex, Ile Ife (OAUTHC) over a period of 10 years and compared the findings with the results from other parts of the world. METHODS: This was a retrospective cohort review of cases of geographic tongue seen in the Oral Medicine of OAUTHC over the period of 10 years of Oral Medicine practice in the center from May 2007 to May 2017. The diagnosis of GT was made based on its typical clinical presentation. Information retrieved from the case notes included age, sex, presenting complaints, clinical findings, treatment and treatment outcomes. RESULTS: Only 21 cases of GT were diagnosed during the study period, giving a prevalence of 2.1% consisting of 11males and 10 females with mean age of 29.5 ± 13.9 years. About half (10 cases) were diagnosed following routine oral examinations while burning tongue sensation, itchy sensation and taste impairment accounted for the presenting complaints among the symptomatic cases. Lesions were mostly seen in the anterior two-third of the tongue (9 cases). All patients responded well to topical steroids. CONCLUSION: This study had shown that GT was more prevalent in younger age group with slight male predilection. More than half of patients presented with symptoms. Successes were recorded with topical steroids.